2023
DOI: 10.3390/jrfm16100436
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Non-Performing Loans in a Small Island Economy of Fiji: Accounting for COVID-19, Bank-Type, and Globalisation

Shasnil Avinesh Chand,
Ronald Ravinesh Kumar,
Peter Josef Stauvermann

Abstract: An increase in non-performing loans and bad debts in the banking sector can make banks vulnerable to a loss of confidence among customers and other banks and a banking collapse. The recent pandemic (COVID-19) and the evolving globalisation can affect bank operations, although the effects may depend on the type of banks and other bank-specific factors. In this paper, we revisit the topic on the determinants of non-performing loans of banks in a small island economy of Fiji over the period 2000 to 2022. We apply… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…Individuals receiving remittances often deposit these funds into their local bank accounts, expanding the bank's pool of funds and enabling the bank to extend loans and engage in investment activities. In one study on banks in Fiji, Chand et al (2021) found a positive correlation between remittances and bank stability, and in another (Chand et al 2023), they observed a negative association between remittances and non-performing loans, indicating that remittances support banking operations. Similarly, Ayhan and Toufaili (2021) examined the relationship between remittances and bank profitability for banks in Lebanon, and they found a positive relationship.…”
Section: Remittances (Rems)mentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals receiving remittances often deposit these funds into their local bank accounts, expanding the bank's pool of funds and enabling the bank to extend loans and engage in investment activities. In one study on banks in Fiji, Chand et al (2021) found a positive correlation between remittances and bank stability, and in another (Chand et al 2023), they observed a negative association between remittances and non-performing loans, indicating that remittances support banking operations. Similarly, Ayhan and Toufaili (2021) examined the relationship between remittances and bank profitability for banks in Lebanon, and they found a positive relationship.…”
Section: Remittances (Rems)mentioning
confidence: 99%
“…Following a few recent studies (Theiri and Hadoussa 2023;Chand et al 2021Chand et al , 2023, we specify the profitability model as follows:…”
Section: Model Specificationsmentioning
confidence: 99%